La nostalgia de Dios en los Salmos 42-43. Intertextualidades literarias e iconográficas - Blunda , Jorge (Antiguo Oriente, 2025)
This contribution focuses on the figure of the deer or hind used in Ps. 42:2 to express the experience of the worshiper and his relationship with the divinity. The literary features of the Psalm will be analyzed and some possible relations with texts of the ancient Middle East and with images documented in the iconography of the Southern Levant will be highlighted. Examination of these intertextualities will contribute to a better understanding of the meaning of such images in biblical literature and the purpose for which they are used; it may also provide some clues to the history of the literature and religion of Israel. Since the image in discussion is found in several pieces of glyptics conspicuously circumscribed in a short period and in rather limited zone, the article postulates that both the Psalm and the seals mentioned would have been produced in monarchic times and during the Assyrian period, in social milieus linked to the court of Judah.